Facing Inequalities in a Communist Country: The Case of Peasant Poverty in the Socialist Republic of Slovenia - Lazarevic, Zarko (Studia Historiae Oeconomicae, 2025)
This article examines how socialist Slovenia produced, obscured, recognized, and partially mitigated peasant poverty. While the official ideology equated full employment, nationalization, and subsidized services with the eradication of poverty, policy and practice relied on euphemisms (“materially deprived”) and framed inequality as transitional. Tracing four political periods (1945–1990), it shows how debates within the Communist Party, measurement via living-cost baskets, exposed persistent disparities, especially between urban and rural populations. A bimodal agricultural strategy privileges state agricultural enterprises and marginalizes small private farms drives deagrarization and rural vulnerability. Households responded through part-time farming (pluriactivity), while gradual, uneven integration into health, pension, and family benefits only culminated in the 1980s. Regional policies have softened but have not erased structural gaps. This article argues that socialist egalitarianism simultaneously compressed and reproduced inequalities in its own way, leaving peasants particularly exposed.